A UNIQUE HYBRID RENAL MONONUCLEAR PHAGOCYTE ACTIVATION PHENOTYPE IN MURINE SLE NEPHRITIS - Bethunaickan, Ramalingam (2011)
Renal infiltration with mononuclear cells is associated with poor prognosis in SLE. A renal macrophage/dendritic cell signature is associated with onset of nephritis in NZB/W mice and immune modulating therapies can reverse this signature and the associated renal damage despite ongoing immune complex deposition. In nephritic NZB/W mice renal F4/80(hi)/CD11c(int) macrophages are located throughout the interstitium whereas F4/80(lo)/CD11c(hi) dendritic cells accumulate in perivascular lymphoid aggregates. We show here that F4/80(hi)/CD11c(int) renal macrophages have a Gr1(lo)/Ly6C(lo)/VLA4(lo)/MHCII(hi)/CD43(lo)/CD62L(lo) phenotype, different to that described for inflammatory macrophages. At nephritis onset F4/80(hi)/CD11c(int) cells upregulate cell surface CD11b, acquire cathepsin and MMP activity and accumulate large numbers of autophagocytic vacuoles; these changes reverse after induction of remission. Latex bead labeling of peripheral blood Gr1(lo) monocytes indicates that these are the source of F4/80(hi)/CD11c(int) macrophages. CD11c(hi)/MHCII(lo) dendritic cells are found in the kidneys only after proteinuria onset, turnover rapidly, and disappear rapidly after remission induction. Gene expression profiling of the F4/80(hi)/CD11c(int) population displays increased expression of pro-inflammatory, regulatory and tissue repair/degradation associated genes at nephritis onset that reverses with remission induction. Our findings suggest that mononuclear phagocytes with an aberrant activation profile contribute to tissue damage in lupus nephritis by mediating both local inflammation and excessive tissue remodeling.